“Thinking alone hurts”. A Systemization of the Experience of the International Group of Doctoral Students working on and from Central America - Alpízar Lobo, Natasha (2025)
The International Group of Doctoral Students working on and from Central America (DOCAX) emerged in 2022 with the aim of creating a space for support and dialogue with students from different doctoral programmes who carry out research in the region. This article aims to formalise the experience we have had as a group, using materials such as notes, photographs, online and in-person meetings, presentations at various events, and a questionnaire that was applied to members in July 2024. Through these, we describe the founding story and characteristics of DOCAX. At the same time, we also wish to highlight the feelings of loneliness and isolation that we suffered during our doctoral programmes, as well as the difficulties, risks and situations of violence that we faced while doing research in Central America. For these reasons we identify with the phrase “thinking alone hurts” from the poem “Estudio con algo de tedio” by Roque Dalton. From this starting point and through the DOCAX group, we have attempted to question the ways in which research is tainted by individualism, as well as the neglect we have often suffered from academic institutions. In this sense, we highlight peer support, cathartic spaces, affective approaches, as well as interdisciplinary exchange, critical reflection about ways to think about or imagine the region, and strategies of prevention and care in our research.